Cellular interactions with bacterial cellulose: Polycaprolactone nanofibrous scaffolds produced by a portable electrohydrodynamic gun for point-of-need wound dressing - GÜNDÜZ, OĞUZHAN (WILEY, 2018)
Electrospun nanofibrous scaffolds are promising regenerative wound dressing options but have yet to be widely used in practice. The challenge is that nanofibre productions rely on bench-top apparatuses, and the delicate product integrity is hard to preserve before reaching the point of need. Timing is critically important to wound healing. The purpose of this investigation is to produce novel nanofibrous scaffolds using a portable, hand-held gun, which enables production at the wound site in a time-dependent fashion, thereby preserving product integrity. We select bacterial cellulose, a natural hydrophilic biopolymer, and polycaprolactone, a synthetic hydrophobic polymer, to generate composite nanofibres that can tune the scaffold hydrophilicity, which strongly affects cell proliferation. Composite scaffolds made of 8 different ratios of bacterial cellulose and polycaprolactone were successfully electrospun. The morphological features and cell-scaffold interactions were analysed using scanning electron microscopy. The biocompatibility was studied using Saos-2 cell viability test. The scaffolds were found to show good biocompatibility and allow different proliferation rates that varied with the composition of the scaffolds. A nanofibrous dressing that can be accurately moulded and standardised via the portable technique is advantageous for wound healing in practicality and in its consistency through mass production.
Keywords: bacterial cellulose; electrohydrodynamic; electrospinning; polycaprolactone; wound dressing; FIBER DIAMETER; IN-VITRO; PROLIFERATION; BIOCOMPATIBILITY; MATRIX; CELLS; BONE; MATS